Implementasi Dakwah Inklusif sebagai Bagian dari Pendidikan Islam bagi Penyandang Disabilitas - Gifary, Arie; Komara, Endang; Koswara, Nandang; Helmawati, Helmawati (Prodi Pendidikan Keagamaan Islam, 2025)
This study aims to explore the level of accessibility to religious preaching for persons with disabilities within the Islamic Da'wah Center (PUSDAI) of West Java Province. Using a descriptive qualitative approach with a case study method, data were collected through observation, in-depth interviews, and documentation. The findings reveal that physical facilities and preaching media at PUSDAI are not yet fully disability-friendly. Visually and hearing-impaired individuals still face obstacles in accessing religious content due to the absence of supporting services such as sign language interpreters, alternative texts, braille materials, or audio-based resources. Moreover, PUSDAI’s digital platforms do not yet offer assistive technology features that would facilitate access for persons with disabilities. These findings indicate a gap between the ideals of inclusive preaching and current on-ground practices, which have yet to fully support the rights of people with disabilities. Although PUSDAI management has expressed openness to change, there is still no concrete policy framework to support inclusive religious services. This study recommends strategic planning based on inclusivity, multisector collaboration, and accessibility audits as initial steps toward improvement. The conclusion emphasizes the need for preaching approaches that are just, participatory, and oriented toward fulfilling the religious rights of people with disabilities.